Book Review: Financial Counseling - Timi Jorgensen (Journal of Financial Therapy, 2018)
This full-service book provides a historically-situated, systemic introduction of the financial counseling profession and an overview of the financial counseling process. The 14 chapters are a compilation of articles written by 26 of the best minds in financial counseling, therapy, planning, as well as psychology and consumer economics. These experts in practice, education, and research take turns chiming in on poignant topics that range from the history of the profession to client communication, and from self-care for counselors to theoretical and practical tips. This book review overviews highlights of this book.
Keywords: book review; financial counseling